Compound Phyllanthus urinaria L Inhibits HBV-Related HCC through HBx-SHH Pathway Axis Inactivation. (24th March 2019) - Li, Yun; Jiang, Mingjie; Li, Mingshun; Chen, Yingjie; Wei, Chunshan; Peng, Lisheng; Liu, Xinliang; Liu, Zhen; Tong, Guangdong; Zhou, Daqiao; He, Jinsong
Abstract : Compound Phyllanthus urinaria L (CP) is a traditional formula widely used in clinical practice for hepatocellular carcinoma (HCC), especially HBV-related HCC. HBx, HBV X gene encoded X protein, has positive correlation with the abnormal SHH pathway in HBV-related HCC. So, we predicted that CP has the capability of anti-HBV-related HCC maybe via inactivating the HBx-Hedgehog pathway axis. HepG2-HBx cells, HBx overexpression, were treated with CP (70 μ g/ml and 35  μ g/ml, respectively) for 48 hours and the mice which received the HepG2-HBx cells were treated with CP (625mg/kg and 300 mg/kg, respectively) for 17 days to evaluate the effect of CP on HBV-related HCC. HBx could accelerate HepG2 cells proliferation, clone formation, and migration in vitro and also could strengthen tumor growth in mice. However, CP could significantly decrease HepG2-HBx cells proliferation, clone formation, and migration in vitro and also could inhibit tumors growth in mice in a dose-dependent manner. Mechanism studies suggested that HBx upregulated the mRNA and proteins expression of Sonic hedgehog (SHH), transmembrane receptor patched (PTCH-1), smoothened (SMO), oncogene homolog transcription factors-1 (GLI-1), and oncogene homolog transcription factors-2 (GLI-2), which are compositions of the SHH pathway. CP could inhibit the mRNA and proteins expression of SHH, PTCH-1, GLI-1, and HBx. It may be one of the underlying mechanisms of CP to delay the HBV-related HCC development through the HBx-SHH pathway axis inactivation.